SPECIFIC DENTAL TREATMENT OF FEMALE PATIENTS WITH BACTERIAL VAGINOSIS - А. Shulzhenko; E. Krutikova; L. Ostrovska; T. Petrushanko (Ukrainian Medical Stomatological Academy, 2017)
Inflammatory and dystrophic inflammatory periodontal diseases are the syndrome manifestation of such common diseases as diabetes mellitus, hyper-and hypothyroidism, gastric and duodenal ulcers, coronary heart disease and a number of other somatic pathologies. At the same time a number of publications on the relationship between the state of parodontium and urogenital diseases are not sufficient to date. Bacterial vaginosis (BV) in women of the childbearing age is considered the most common disease (67-89%) of the urogenital system. The WHO defines bacterial vaginosis as polymicrobial dysbiotic non-inflammatory disease when the specific and quantitative vector of vaginal microflora is shifted to the anaerobic microorganisms. The infectious agents of BV are Gardnerella vaginalis and Atopobium vaginae, capable to the formation of biofilms and are quite resistant to many advanced antibacterial drugs. The paper presents the comparison of the effectiveness of the conventional treatment regimen of gingivitis and periodontitis in women with BV and therapeutic regimen that affects the agents of BV (Gardnerella vaginalis and Atopobium vaginae). Our investigations have proved by evidence the presence of such chronic generalized inflammatory and dystrophic inflammatory periodontal diseases as chronic catarrhal gingivitis, the initial and first-degree periodontitis in all patients with BV. The relevant objective of the study is to substantiate the approach to dental treatment of such patients. The paper was aimed at the development and verification of the effectiveness of dental treatment regimen of women with bacterial vaginosis and manifestation of the inflammatory and dystrophic inflammatory diseases of parodontium.  54 women aged 18 to 45 years with confirmed BV gynecological diagnosis have been examined; dental and gynecological status have been studied, too.  The patients were divided into 2 groups according to the approach to dental treatment: women of Group I (control) received conventional treatment (26 patients), and women from Group II (study) were treated according to the suggested regimen  (28 women). The general therapy included prescription of 50 mg Fluconazole once a day during 7 days and 250 mg Metronidazole every 6 hours during 5 days (Group I); 150 mg Clindamycin every 6 hours during 5 days, 1 tab. Calcium-D3 Nycomed during the evening meal over 30 days (Group II), and "Symbiter Acidophilic Concentrated" probiotic during 21 days. Local drug treatment of women of Group I included oral baths with Stomatofìt after morning and evening personal hygiene procedures during 7 days and applications with "Metrogil-denta" gel on the gums during 7 days and patients of Group II were supplementary prescribed with 1 tab. Lizak every 6 hours during 5 days; at the end of treatment with Stomatofìt and "Metrogil-denta" applications with "Simbiter omega" probiotic on the gums in silicone trays at night during 21 days were prescribed. Parodontal status was determined using the РМА indices (in Parma modification), Leus comprehensive parodontal index (CPI), Schiller-Pisarev's tests, Svrakov's value at the moment of admission and after 3 months. After 90 days of treatment gingival inflammation was not eliminated in nearly half of the women of the control group. Decrease of the РМА index has been observed in 16,15% of patients, and CPI index was 1,33 times lower. Noteworthy, evaluation of the state of parodontium in patients of the study group in dynamic observation has shown the regress of pathological progress in the parodentium. In Group II the РМА index decreased by 48, 68% and CPI index was 6,3 times lower, indicating about more higher efficacy of treatment regimen, aimed at the affecting the infectious agents of BV as the concomitant somatic disease.